Pengaruh Jenis Dan Suhu Pelarut Pada Preparasi Pelepah Sawit Sebagai Bahan Baku Wood Plastic Composite - Dian Anggraini Purba; Zultiniar Zultiniar; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Palm frond biomass is potentially to be used as a filler for plastic-wood composite products known as Wood Plastic Composite (WPC). This study aims to determine the influence of solvent type and temperature on preparation of palm frond as raw material of WPC. The palm frond which has been reduced to powder is dried in open air for ± 24 hours. Further drying uses an oven at 1050C where the final water content of the powder is 5%. Furthermore, the material is scaled down again in size to obtain 60 mesh. Palm oil powder is extracted for 15 minutes using solvent and high temperature. The solvent variations used are NaOH and H2O2 with concentration of 1 N while the variation temperature of extraction step is 100oC, 120oC and 140oC. The results showed that the type of solvent has a relatively significant effect on cellulose content of frond is increasing cellulose level of 13.44% - 22.23%, while the temperature changes did not give significant effect to the increase of fronds cellulose levels. The best preparation results were obtained in the preparation using NaOH solvent at 140 ° C with a cellulose content of 57,47%.Keywords: moisture content, palm frond, preparation, wood plastic composite